Quality of life in patients with relapsed/refractory multiple myeloma during ixazomib-thalidomide-dexamethasone induction and ixazomib maintenance therapy and comparison to the general population - Ludwig, Heinz; Pönisch, Wolfram; Knop, Stefan; Egle, Alexander; Hinke, Axel; Schreder, Martin; Lechner, Daniel; Hajek, Roman; Gunsilius, Eberhard; Petzer, Andreas; Weisel, Katja; Niederwieser, Dietger; et al. (Leukemia & lymphoma, 2020)
This trial evaluated quality of life (QoL) using the EORTC QLQ-C30 and the EORTC QLQ-MY20 instruments in 90 patients with relapsed/refractory multiple myeloma during induction and maintenance therapy with eight cycles of ixazomib-thalidomide-dexamethasone, followed by 12 months of ixazomib maintenance therapy. When patient's baseline QoL was compared with data of the general population, a significant impairment in health-related QoL, physical, role, and social functioning and several other dimensions, as well as more pain and fatigue, was noted. Induction therapy resulted in significant improvement of pain and worsening of neuropathy, with no significant variation of other parameters. During maintenance treatment, scores for most dimensions including health-related QoL, physical functioning and pain, improved, while for neuropathy no improvement was observed. Time to deterioration (≥10 score points) of health-related QoL, physical functioning, pain, and neuropathy was distinctly shorter than time to progression. Health-related QoL and physical functioning at baseline correlated with overall survival.
Keywords: Thalidomide; dexamethason; Humans; Quality of Life; ixazomib; Multiple Myeloma; sloučeniny boru; protokoly protinádorové kombinované chemoterapie; Glycine; glycin; lidé; kvalita života; mnohočetný myelom; thalidomide; relapsed/refractory disease; Dexamethasone; Antineoplastic Combined Chemotherapy Protocols; Boron Compounds; quality of life; Multiple myeloma; thalidomid